Factors associated with contracted services of Chinese family doctors from the perspective of medical staff and consumers: a cross-sectional study - Huanyan Wang; Lei Shi; Xuanye Han; Jinchan Zhang; Yuanshuo Ma; Xi Yang; Ming Liu; Lihua Fan; Fengge Lou (BMC, 2019)
Abstract Background The family doctor system has developed rapidly all over the world, and in the past few years, China has actively explored family doctor-type contracted services. This study aimed to explore the related factors of Contracted Family Doctors Services (CFDS) from the perspectives of medical staff and consumers, and to provide a stronger basis for the development and promotion of CFDS. Methods A combination of quantitative and qualitative methods were used in this study. A self-reported questionnaire was designed through a literature analysis, group discussions, expert consultations and a pre-investigation, and conducted among community health service providers in 12 community health service centres across four provinces of China. A total of 389 participants participated, and 320 valid questionnaires were obtained, with an effective response rate of 82.3%. A total of 36 consumers participated in in-depth interviews, and the effective rate was 100.0%. An exploratory factor analysis, a confirmatory factor analysis, inductive methods, and expert consultations were used to analyse the related factors of CFDS. Results The related factors of CFDS from the perspectives of medical staff were divided into four dimensions, with the following weighting coefficients: national government factors (31.9%), community health service agency factors (24.7%), consumer-related factors (22.6%), and contracted doctor-related factors (20.8%). The related factors of CFDS from the perspectives of consumers were divided into four dimensions, with the following frequency sequence: national government factors, contract doctor-related factors, community health service agency factors, and consumers-related factors. National government factors played an important role in CFDS from the perspectives of medical staff and consumers. Conclusions The related factors of CFDS were the same from the perspective of medical staff and consumers, but the weight of each factor was different. The development of CFDS is inseparable from the support of policies. It is suggested that the government should strengthen the publicity of CFDS, expand the coverage, introduce personalised contract programs that meet the needs of different groups, and promote the rapid development of CFDS.